TAXPAYER COMPLIANCE REVIEWED FROM TAXPAYER AWARENESS, TAXPAYER KNOWLEDGE, AND TAX AUDIT (STUDY AT THE OFFICE OF THE AGENCY OF REVENUE, FINANCIAL MANAGEMENT, AND REGIONAL ASSETS (BPPKAD) CITY OF SURAKARTA) - Aditya Widiatama; Sudarwati Sudarwati; Fithri Marwati; Sitti Mukarromah; Afiefah Sulistyowati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Taxpayer compliance is critical for creating orderly tax payments in Indonesia. Several factors can influence taxpayer compliance. Individual or internal taxpayers, as well as foreign taxpayers, can provide these factors. The goal of this study was to look into the impact of taxpayer awareness, knowledge, and tax audits on taxpayer compliance. The data used in this study are primary data gathered from questionnaires sent to employees of the Surakarta City Revenue, Financial Management, and Regional Assets Office (BPPKAD). The sample size is limited to 60 responders. Purposive sampling is utilized, which means that the sample technique is determined by particular factors. The validity test, reliability test, multiple linear regression, and statistical test t test were employed in this study. The SPSS for Windows version 24 program was used for hypothesis testing. Data analysis results reveal that taxpayer awareness, taxpayer knowledge, and tax audit all have an impact on taxpayer compliance. Each variable of taxpayer awareness, taxpayer knowledge, and tax audit has an impact on taxpayer compliance to some extent. This research will be utilized as a reference for future decision making, particularly in an effort to promote taxpayer compliance. . Keywords: Taxpayer awareness, Taxpayer knowledge, Tax audit, Taxpayer compliance.